Influence of carbon black on the Payne effect of filled natural rubber compounds. (8th February 2021) - Shi, Xuanyu; Sun, Shihao; Zhao, An; Zhang, Haimo; Zuo, Min; Song, Yihu; Zheng, Qiang
Abstract: The incorporation of carbon black (CB) in natural rubber (NR) enhances the Payne effect while the mechanism has not been clearly clarified so far. Herein the Payne effect of CB filled NR compounds under large strain amplitudes is investigated via simultaneous measurement of rheological response and electrical conduction. Low temperature and high frequency accelerate the Payne effect. The destruction and recovery of CB agglomerates are not synchronized with the appearance of the Payne effect, indicating that the structural evolution of the filler phase is not the main factor dominating the Payne effect. The investigation would be illuminating for understanding the molecular mechanisms of strain softening in rubber nanocomposites. Graphical abstract: Image 1